2019
DOI: 10.3390/g10040043
|View full text |Cite
|
Sign up to set email alerts
|

Can Behavioral “Nudges” Improve Compliance? The Case of Colombia Social Protection Contributions

Abstract: The Government of Colombia imposes a variety of taxes that must be paid by individual wage earners, called in their entirety “social protection contributions”. Since 2007 individual payments have been collected using an on-line mechanism. In order to improve compliance, the Government used a controlled field experiment in which various “pop-up messages” were sent to individuals when making their on-line payments, as behavioral “nudges”. We examine the impact of these nudges on individual reporting behavior. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The results highlight multiple mechanisms of tax evasion and tax avoidance used by large corporations and wealthy taxpayers including tax havens, the underground economy, aggressive tax planning, parallel financial markets, and cryptocurrencies. This paper also contributes to the current debate on tax compliance (Jiang et al, 2022;Vainre et al, 2020;Alm et al, 2019;Fonseca and Grimshaw, 2017;OECD, 2004) by suggesting potential strategies to reduce tax evasion and tax avoidance. These strategies include preventive actions, active monitoring of compliance indicators, peer reporting and international cooperation.…”
Section: Discussionmentioning
confidence: 85%
“…The results highlight multiple mechanisms of tax evasion and tax avoidance used by large corporations and wealthy taxpayers including tax havens, the underground economy, aggressive tax planning, parallel financial markets, and cryptocurrencies. This paper also contributes to the current debate on tax compliance (Jiang et al, 2022;Vainre et al, 2020;Alm et al, 2019;Fonseca and Grimshaw, 2017;OECD, 2004) by suggesting potential strategies to reduce tax evasion and tax avoidance. These strategies include preventive actions, active monitoring of compliance indicators, peer reporting and international cooperation.…”
Section: Discussionmentioning
confidence: 85%
“…Also, this work often finds that more audits increase compliance but in a non‐linear way, so that the deterrent effect diminishes with higher audit rates. My controlled field experiments in Colombia with Carlos Ortiz and Diana Rocha have found that telling individuals that they will be subject to “more scrutiny” via a message from the tax authority has a positive impact on compliance, even if small, variable, and fleeting (Alm, Ortiz, and Rocha ). However, there are also other field studies with these messages that find no impact, and sometimes even a conflicting impact, on compliance (Slemrod, Blumenthal, and Christian ; Hallsworth ).…”
Section: “To Increase Tax Compliance Increase Enforcement”mentioning
confidence: 99%